The dental microwear texture of wild boars from Japan reflects inter- and intra-populational feeding preferences - Miyamoto, Kohga; Kubo, Mugino O.; Yokohata, Yasushi (Frontiers in Ecology and Evolution, 2022)
Dental microwear texture analysis (DMTA) is rapidly expanding for the dietary estimation of extinct animals. There has been an extensive accumulation of microwear texture data from herbivorous mammals, especially for ruminant artiodactyls, but suids are still underrepresented. Microwear varies depending on the diet, and suids are naturally more flexible than other artiodactyls, thus their microwear is prone to greater variability. In this study, we examine the tooth microwear texture of wild boars from Toyama Prefecture, Japan, for which detailed ecological and dietary information by stomach content analysis is available. We first investigated 205 individuals of wild-shot Toyama boars with known sex, age class, localities (the eastern high latitude region vs. the western low latitude region), and season of collection. The tooth surfaces of boarlets were rougher than that of juveniles and adults. Decrease of surface roughness with age implied that the frequency of tooth-tooth contact, which seemed to result in cracking of enamels and thus rough surfaces, decreased after the boars started feeding on solid foods (food-tooth contact), with progressive involvement of rooting behavior in mature adults. We further found that surface roughness showed significant differences between localities, with the western Toyama boars having flatter surfaces possibly due to the fact that they involved in more rooting and feeding on soil-contaminated rhizomes than the eastern ones, as implied by the available stomach content data. The frequency of rooting was also evident in the broader comparison among Japanese boar populations with different habitat environments. The mainland boars inhabiting deciduous broad-leaved forests had flatter and less rough tooth surfaces than those in subtropical evergreen broad-leaved forests of southern islands. This corresponds to the fact that above-ground dietary resources were more available in the habitat of the southern island boars, where crops like succulent vegetables and fruits as well as naturally fallen acorns were abundant, whereas underground plant parts were the dominant diet component for the mainland boars. This study proved that DMTA can identify the difference in foraging modes in suids and paves the way to estimate frequency of rooting, which is informative to infer breeding methods of boars/pigs from archaeological sites.